A new hybrid nonlinear congruential number generator based on higher functional power of logistic maps - Çeçen, Songül; Demirer, R. Murat; Bayrak, Coşkun (PERGAMON-ELSEVIER SCIENCE LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND, 2009)
We propose a nonlinear congruential pseudorandom number generator consisting Of summation of higher order composition of random logistic maps under certain congruential mappings. We change both bifurcation parameters of logistic maps in the interval of U = [3.5599,4) and coefficients of the polynomials in each higher order composition of terms Lip to degree d. This helped us to obtain a perfect random decorrelated generator which is infinite and aperiodic. It is observed from the simulation results that our new PRNG has good uniformity and power spectrum properties with very flat white noise characteristics. The results are interesting, new and may have applications in cryptography and in Monte Carlo simulations. Published by Elsevier Ltd.